Drug Delivery Systems for Hedgehog Inhibitors in the Treatment of SHH-Medulloblastoma - Caimano, Miriam; Lospinoso Severini, Ludovica; Loricchio, Elena; Infante, Paola; Di Marcotullio, Lucia (Frontiers in Chemistry, 2021)
Medulloblastoma (MB) is a highly aggressive pediatric tumor of the cerebellum. Hyperactivation of the Hedgehog (HH) pathway is observed in about 30% of all MB diagnoses, thereby bringing out its pharmacological blockade as a promising therapeutic strategy for the clinical management of this malignancy. Two main classes of HH inhibitors have been developed: upstream antagonists of Smoothened (SMO) receptor and downstream inhibitors of GLI transcription factors. Unfortunately, the poor pharmacological properties of many of these molecules have limited their investigation in clinical trials for MB. In this minireview, we focus on the drug delivery systems engineered for SMO and GLI inhibitors as a valuable approach to improve their bioavailability and efficiency to cross the blood–brain barrier (BBB), one of the main challenges in the treatment of MB.